Pengembangan Media Pembelajaran E-book untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Akidah Akhlak di MA Assalafiyyah Yogyakarta - Islamiyah, Ulya; Hairiyah, Hairiyah; Susilowati, Ika Tri; Nawangsasi, Esthi (Universitas Alma Ata, 2025)
Student learning outcomes can be influenced by appropriate learning media, with this, researchers are developing e-book learning media which includes multimedia. The aim of this research is to find out how e-book products are developed, how appropriate the e-book products are developed and how the use of e-book products developed is influenced in improving student learning outcomes in the subject of moral beliefs.The method used is the Research and Development method with the ADDIE model. The research population was class XI students at MA Assalafiyyah Mlangi Yogyakarta. The experimental group and control group consisted of 49 students who were determined using a purposive sampling technique. The experimental study used quasi experimental research with a nonequivalent control group design.The results of the development were carried out by analyzing students' needs regarding learning media, creating product designs, product development using the Canva application with the help of Heyzine to create multimedia effects, product implementation for students, and product evaluation.Product feasibility results are demonstrated through validation by experts and student response questionnaires. Material validation shows a figure of 77.7% (very feasible), media validation shows a figure 83,75% (very feasible), validation of test instruments shows a figure of 75% (feasible), questionnaire validation shows a figure of 75% (feasible) and student response questionnaire data shows a figure of 88.85% (very feasible). So that the e-book development product is declared feasible.The results of the research using the t test obtained a significance value of 0.042. So 0.042 < 0.05, which means that in this study there is a significant difference between classes that use e-book media and classes that do not use e-book media in improving student learning outcomes in the subject of moral beliefs.Keywords: e-book media, RnD, ADDIE, Learning Outcomes